Бонапарт: повесть / Александр Дюма - Дюма Александр (Закон власти, 2008)
Экземпляры: ф.15 (20150925) / Инвентарный номер: 56483 / Цена: / Сис.шифр: 84(4Фра)-44 / Авт.знак: Д 96 / ГРНТИ: 17.82.31 / ББК: 84(4Фра)-44